Walking For Health: Improving Exercise Awareness Among The Community Of Malilingi - Muhammad Fadli; Ahmad Zakaria; Fathurrahman Fathurrahman; Alif Hariyadi Hardi (Jurnal Dharma Abdi Lestari (JDAL), 2025)
Public health is strongly influenced by lifestyle, including exercise habits. Walking for health (jalan sehat) is a simple, low-cost physical activity that can be performed by people of all ages. This community service study aims to increase awareness of exercise and optimize the use of public facilities through walking activities in Malilingi Village, Bantaeng Regency. A participatory action approach was employed, involving the community as planners, implementers, and evaluators. Activities included health education, organized walking sessions, and evaluation of facilities and community participation. Results showed increased community participation, the establishment of the Malilingi Healthy Walking Community, and more effective use of public spaces. In addition to improving physical fitness, the activities strengthened social interactions, solidarity, and environmental awareness. These findings align with the Health Promotion Model and the concept of social capital, emphasizing the importance of environmental interventions and active community participation in fostering healthy behaviors. Walking for health in Malilingi Village proves to be an effective community-based health promotion strategy.